The Influence of Leadership Style and Personality Type on Employee Work Productivity - Badrianto, Yuan; Andriyani, Apri; Young, Felina C. (DPPM Universitas Pelita Bangsa, 2024)
This study aims to determine the effect of leadership style and personality type on employee productivity. To increase productivity, of course, a leader is needed who can have a positive influence on his employees, so that they can carry out their duties with the expected results and achieve the goals that have been determined. Apart from leadership, another thing that can increase productivity is personality type. This research uses quantitative methods. The data collection method used in this study includes data derived from distributed questionnaires. The sampling technique distributed is a probability sampling technique by means of saturated sampling, so that the number of samples is the same as the total population of 51 respondents. The results of the study indicate that the leadership style partially affects the work productivity of employees. Personality type partially influences employee work productivity, Leadership Style and Personality Type simultaneously affect employee work productivity.